2020
DOI: 10.1182/bloodadvances.2020003121
|View full text |Cite
|
Sign up to set email alerts
|

Durable ibrutinib responses in relapsed/refractory marginal zone lymphoma: long-term follow-up and biomarker analysis

Abstract: Advanced marginal zone lymphoma (MZL) is an incurable B-cell malignancy dependent on B-cell receptor signaling. The phase 2 PCYC-1121 study demonstrated the safety and efficacy of single-agent ibrutinib 560 mg/d in 63 patients with relapsed/refractory MZL treated with prior rituximab (RTX) or rituximab-based chemoimmunotherapy (RTX-CIT). We report the final analysis of PCYC-1121 with median follow-up of 33.1 months (range: 1.4-44.6). Overall response rate (ORR) was 58%; median duration of response (DOR) was 27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
70
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 47 publications
6
70
1
Order By: Relevance
“…Novel therapeutic strategies are being currently explored in ongoing clinical trials. Noy et al recently reported on long-term safety and efficacy of single agent ibrutinib, a Bruton’s tyrosine kinase inhibitor, in a cohort of relapsed/refractory MZLs previously treated with rituximab, alone or in combination [ 81 ]. Preliminary clinical evidence indicated that PI3K inhibitors copanlisib and umbrasilib showed excellent activity in MZL [ 82 ].…”
Section: Primary Pulmonary Marginal Zone Lymphoma Of Mucosa-associmentioning
confidence: 99%
“…Novel therapeutic strategies are being currently explored in ongoing clinical trials. Noy et al recently reported on long-term safety and efficacy of single agent ibrutinib, a Bruton’s tyrosine kinase inhibitor, in a cohort of relapsed/refractory MZLs previously treated with rituximab, alone or in combination [ 81 ]. Preliminary clinical evidence indicated that PI3K inhibitors copanlisib and umbrasilib showed excellent activity in MZL [ 82 ].…”
Section: Primary Pulmonary Marginal Zone Lymphoma Of Mucosa-associmentioning
confidence: 99%
“…Grade ≥ 3 AEs occurred in 71% of patients including grade ≥ 3 infection in 22%. 109 Most adverse events were grade 1/2, and grade ≥3 events included also anemia (16%), pneumonia (8%) and fatigue (6%). Ibrutinib is thus an excellent option for older patients whose MZL is refractory to rituximab monotherapy.…”
Section: Relapsed/refractory Diseasementioning
confidence: 95%
“…In MZL, the use of ibrutinib is more compelling, as it attains 58% ORR (81% for those pre-treated with rituximab only) with a median PFS of 16 months and median duration of response of 28 months. 108 , 109 It is now FDA-approved for use in relapsed/refractory MZL. Ibrutinib is tolerable among older patients, with the oldest patient enrolled in a phase 2 trial being 92 years old.…”
Section: Relapsed/refractory Diseasementioning
confidence: 99%
“…In MZL, the frequency of MYD88 mutation is less than 5% while ORR to ibrutinib 48%, suggesting that responses are independent of MYD88 mutation status [ 204 , 205 ]. Notwithstanding, in a recent analysis in R/R MZL, patients with TNFAIP3 mutations had better responses to ibrutinib and those with MYD88L265P mutations had longer PFS [ 206 ]. Conversely, patients with mutations in KMT2D and CARD11 derived less benefit from treatment.…”
Section: Relapsed and Refractory Diseasementioning
confidence: 99%